The Ossetes - Foltz, Richard, 1961- (London)
xvi, [1] sayfa
Keywords: “The Ossetes, a small nation inhabiting two adjacent states in the central Caucasus, are the last remaining linguistic and cultural descendants of the ancient nomadic Scythians who dominated the Eurasian steppe from the Balkans to Mongolia for well over one thousand years. A nominally Christian nation speaking a language distantly related to Persian, the Ossetes have inherited much of the culture of the medieval Alans who brought equestrian culture to Europe. They have preserved a rich oral literature through the epic of the Narts, a body of heroic legends that shares much in common with the Persian Book of Kings and other works of Indo-European mythology. This is the first book devoted to the little-known history and culture of the Ossetes to appear in any Western language. Charting Ossetian history from Antiquity to today, it will be a vital contribution to the fields of Iranian, Caucasian, Post-Soviet and Indo-European Studies“ --